Assessment of Minimal Residual Disease in Ewing Sarcoma. (12th March 2012) - Wagner, Lars M.; Smolarek, Teresa A.; Sumegi, Janos; Marmer, Daniel
Abstract : Advances in molecular pathology now allow for identification of rare tumor cells in cancer patients. Identification of this minimal residual disease is particularly relevant for Ewing sarcoma, given the potential for recurrence even after complete remission is achieved. Using RT-PCR to detect specific tumor-associated fusion transcripts, otherwise occult tumor cells are found in blood or bone marrow in 20–30% of Ewing sarcoma patients, and their presence is associated with inferior outcomes. Although RT-PCR has excellent sensitivity and specificity for identifying tumor cells, technical challenges may limit its widespread applicability. The use of flow cytometry to identify tumor-specific antigens is a recently described method that may circumvent these difficulties. In this manuscript, we compare the advantages and drawbacks of these approaches, present data on a third method using fluorescent in situ hybridization, and discuss issues affecting the further development of these strategies.